Integrated Continuing Professional Teacher Development (CPTD) Model - Thusi, Nisi; Costa, King (My University, 2020)
CPTD (Continuing Professional Teacher’s Development) is the method of recording and reporting the skills, qualifications and knowledge acquired by teachers when they work. The purpose of this model is to present a holistic and integrated approach to current initiatives of educator development. This approach connects efforts of the Basic Department of Education, which is the custodian and regulator of educator development in South Africa. The model is made up of 4 Tiers or levels which sequentially feed into each other in a progressive manner. The first Tier represents the fundamental principles of CPTD at the Department of Basic Education. The aim is to constantly improve the quality of teaching and learning by empowering, motivating and training educators using a standardised CPTD programme. The second Tier ensured that the principles set by the Department of Basic Education are advanced through a statutory body within the sector, known as South African Council of Educators (SACE). There is mandate is monitor and manage the CPTD system as the core function to enhance the teaching profession in South Africa. In order to uphold the educator/ teaching profession, SACE prescribes that each educator produce a Personal Development Plan (PDP) file as part of the CPTD system and Portfolio of Evidence (PoE). This PoE provides evidence for the three-year development cycle, with accumulation of required CPTD points. This process of collection and maintenance of professional development points is stored in an Integrated Quality Management System (IQMS), an electronic/computer system managed directly from the SACE offices. The system is access control and login details are provided by SACE to educators who complete. More details about the outcomes of the CPTD programme are discussed under Tier 4.
Keywords: Continued Professional Teacher Development; Department of Basic Education; Professional Development Plans; Schools; South African Council of Educators; Teachers